Identifikasi Litologi Bawah Permukaan Dalam Menentukan Lapisan Keras Menggunakan Metode Geolistrik di Desa Rejomulyo, Lampung Selatan - Rhahmi Adni Pesma; Muhamad Raja Saffath (Program Studi Teknik Geofisika FITK UHO, 2025)
Measurements have been conducted using the Schlumberger configuration Vertical Electrical Sounding (VES) geoelectric method in Rejomulyo Village, South Lampung. This study aims to identify subsurface lithology in determining rocks resembling hard rocks using VES geoelectric data. Primary data collection using Naniura with 6 Vertical Electrical Sounding (VES) points. Each sounding point has an AB/2 length of 150 meters and a MN/2 spacing of 0.5 meters to 10 meters. The distance between VES points is 75-150 m. Data processing in the study used IPI2WIN+IP software. 2D model creation used Surfer software. The types of subsurface rocks found were Tuff Clay, tuff sand, coarse-grained tuff and fine-grained tuff. Then the rock that resembles a hard layer is tuff rock with fine and compact grains with a resistivity value of more than 300 Ωm, namely 323 - 529 Ωm at a depth of 25.6 - 36.6 m, but at the VES 6 point, no layer resembling a hard layer was detected due to the low resistivity value measured at the VES 6 point, namely 228.7 Ωm.